Building Student Loyalty Through Study Program Commitment - Hendra Riofita; Annisa Dwi Khai Yasmin; Muammar Syarqawi; Nabila Maharani; Rahma Dinda Annisa (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2023)
This study aims to determine the effect of study program commitment on student loyalty. This is conducted through a survey. Data are taken from students of the Economics Education Study Program, Teacher Training and Education Faculty of State Islamic University of Sultan Syarif Kasim, Riau by using a questionnaire in the form of google form link and analyzed with SPSS program. The results show that study program commitment has a significant effect on student loyalty. The finding also indicates that the study program commitment and student loyalty can be developed based on social exchange theory.